Pre-clinical development of BCG.HIVA(CAT), an antibiotic-free selection strain, for HIV-TB pediatric vaccine vectored by lysine auxotroph of BCG - Saubi, N; Mbewe-Mvula, A; Gea-Mallorqui, E; Rosario, M; Gatell, J; Hanke, T; Joseph, J (Public Library of Science, 2012)
In the past, we proposed to develop a heterologous recombinant BCG prime-recombinant modified vaccinia virus Ankara (MVA) boost dual pediatric vaccine platform against transmission of breast milk HIV-1 and Mycobacterium tuberculosis (Mtb). In this study, we assembled an E. coli-mycobacterial shuttle plasmid pJH222.HIVACAT expressing HIV-1 clade A immunogen HIVA. This shuttle vector employs an antibiotic resistance-free mechanism based on Operator-Repressor Titration (ORT) system for plasmid selection and maintenance in E. coli and lysine complementation in mycobacteria. This shuttle plasmid was electroporated into parental lysine auxotroph (safer) strain of BCG to generate vaccine BCG.HIVACAT. All procedures complied with Good Laboratory Practices (GLPs). We demonstrated that the episomal plasmid pJH222.HIVACAT was stable in vivo over a 20-week period, and genetically and phenotypically characterized the BCG.HIVACAT vaccine strain. The BCG.HIVACAT vaccine in combination with MVA.HIVA induced HIV-1- and Mtb-specific interferon γ-producing T-cell responses in newborn and adult BALB/c mice. On the other hand, when adult mice were primed with BCG.HIVACAT and boosted with MVA.HIVA.85A, HIV-1-specific CD8+ T-cells producing IFN-γ, TNF-α, IL-2 and CD107a were induced. To assess the biosafety profile of BCG.HIVACAT-MVA.HIVA regimen, body mass loss of newborn mice was monitored regularly throughout the vaccination experiment and no difference was observed between the vaccinated and naïve groups of animals. Thus, we demonstrated T-cell immunogenicity of a novel, safer, GLP-compatible BCG-vectored vaccine using prototype immunogen HIVA. Second generation immunogens derived from HIV-1 as well as other major pediatric pathogens can be constructed in a similar fashion to prime protective responses soon after birth.